Molecular and Optical Properties of Tree-Derived Dissolved Organic Matter in Throughfall and Stemflow from Live Oaks and Eastern Red Cedar - Stubbins, Aron; Silva, Leticia M.; Dittmar, Thorsten; Van Stan, John T. (Frontiers in Earth Science, 2017)
Studies of dissolved organic matter (DOM) transport through terrestrial aquatic systems usually start at the stream. However, the interception of rainwater by vegetation marks the beginning of the terrestrial hydrological cycle making trees the headwaters of aquatic carbon cycling. Rainwater interacts with trees picking up tree-DOM, which is then exported from the tree in stemflow and throughfall. Stemflow denotes water flowing down the tree trunk, while throughfall is the water that drips through the leaves of the canopy. We report the concentrations, optical properties (light absorbance) and molecular signatures (ultrahigh resolution mass spectrometry) of tree-DOM in throughfall and stemflow from two tree species (live oak and eastern red cedar) with varying epiphyte cover on Skidaway Island, Savannah, Georgia, USA. Both stemflow and throughfall were enriched in DOM compared to rainwater, indicating trees were a significant source of DOM. The optical and molecular properties of tree-DOM were broadly consistent with those of DOM in other aquatic ecosystems. Stemflow was enriched in highly colored DOM compared to throughfall. Elemental formulas identified clustered the samples into three groups: oak stemflow, oak throughfall and cedar. The molecular properties of each cluster are consistent with an autochthonous aromatic-rich source associated with the trees, their epiphytes and the microhabitats they support. Elemental formulas enriched in oak stemflow were more diverse, enriched in aromatic formulas, and of higher molecular mass than for other tree-DOM classes, suggesting greater contributions from fresh and partially modified plant-derived organics. Oak throughfall was enriched in lower molecular weight, aliphatic and sugar formulas, suggesting greater contributions from foliar surfaces. While the optical properties and the majority of the elemental formulas within tree-DOM were consistent with vascular plant-derived organics, condensed aromatic formulas were also identified. As condensed aromatics are generally interpreted as deriving from partially combusted organics, some of the tree-DOM may have derived from the atmospheric deposition of thermogenic and other windblown organics. These initial findings should prove useful as future studies seek to track tree-DOM across the aquatic gradient from canopy roof, through soils and into fluvial networks.